2022
DOI: 10.1099/jmm.0.001512
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of the impact of oral contraceptive use on the gut microbiome

Abstract: Introduction. Evidence has linked exogenous and endogenous sex hormones with the human microbiome. Hypothesis/Gap statement. The longitudinal effects of oral contraceptives (OC) on the human gut microbiome have not previously been studied. Aim. We sought to examine the longitudinal impact of OC use on the taxonomic composition and metabolic functions of the gut microbiota and endogenous sex steroid hormones after initiation of OC use. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Several human studies have examined menopausal and/or sex hormone relationships with gut microbial features in general and HIV populations. [12][13][14][15][16][17][18][19][20][21][22] Most of them yielded heterogeneous results, which might be due to differences in population characteristics, such as age, ethnicity and BMI, sample sizes that ranged from 10 to 1,322 women, and sequencing approaches including FIG. 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several human studies have examined menopausal and/or sex hormone relationships with gut microbial features in general and HIV populations. [12][13][14][15][16][17][18][19][20][21][22] Most of them yielded heterogeneous results, which might be due to differences in population characteristics, such as age, ethnicity and BMI, sample sizes that ranged from 10 to 1,322 women, and sequencing approaches including FIG. 4.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is biologically plausible that menopause may affect the gut microbiome via altering the metabolic interactions of certain gut bacteria and estrogens. 11 In recent years, studies on menopause [12][13][14][15][16][17] or sex hormones 12,13,[16][17][18][19][20][21][22] in relation to the gut microbiome have attracted much attention, but they revealed disparate patterns in taxa and functional profiles, and less is known in the context of HIV infection. Our prior work in the Women's Interagency HIV Study (WIHS) reported that, among 432 women with and without HIV, several microbial taxa (eg, Enterobacteriales, Prevotella copri) differed by menopausal status only in WWH.…”
mentioning
confidence: 99%
“…There are several factors affecting SHBG levels: estrogen can increase SHBG levels; testosterone can decrease SHBG levels; age, hypothyroidism can increase SHBG levels; obesity and insulin resistance can decrease SHBG levels. 17,18 Besides, oral contraceptives can significantly increase SHBG levels in females 19 ; in males, SHBG levels decrease in the presence of obesity or diabetes. 9 Study has found that SHBG levels in women with major depression are not significantly altered, 20 which is consistent with the finding in this study that there is no causal relationship between SHBG and major depression in women.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of oral contraceptives fails to alter the overall composition of gut microbiome in healthy women 61 . However, dietary changes affect microbial communities in the gut in terms of both composition and function, which may influence innate and adaptive immune systems of the host.…”
Section: Gut Microbiome and Changes In Its Composition With Menstrual...mentioning
confidence: 99%
“…60 The administration of oral contraceptives fails to alter the overall composition of gut microbiome in healthy women. 61 However, dietary changes affect microbial communities in the gut in terms of both composition and function, which may influence innate and adaptive immune systems of the host. Commensals significantly impact the development and responses of the immune system, and thus, they may also affect outcomes of immunological diseases.…”
Section: Gut Microbiome and Changes In Its Composition With Menstrual...mentioning
confidence: 99%